Effect of replacement of de-oiled rice bran with sweet potato leaf meal on growth performance, digestive enzyme activity and body composition of Labeo rohita (Hamilton, 1822) - Ahmad, Ziahan; Deo, Ashutosh Dharmendra; Kumar, Sarvendra; Ranjan, Amit; Aklakur, Md; Sahu, Narottam Prasad (Indian Journal of Fisheries, 2019)
A 60-days feeding experiment was conducted to evaluate the utilisation of sweet potato leaf meal (SPLM) for replacement of de-oiled rice bran (DORB) in the diets of rohu Labeo rohita (Hamilton, 1822) fingerlings. SPLM has good protein content (22.12%) and digestible energy content (11.81 MJ kg-1). Five iso-nitrogenous (30%) and iso-caloric diets (13.5 MJ kg-1) were prepared by replacing DORB with sweet potato leaf meal (SPLM) at 0% (C), 25% (T1), 50% (T2), 75% (T3) and 100% (T4). Each dietary treatment was tested in triplicates with 12 fingerlings per tank, following completely randomised design. The growth performance and feed utilisation parameters viz., weight gain % (WG), specific growth rate (SGR), protein efficiency ratio (PER) and feed conversion ratio (FCR) were not significantly different (p>0.05) among treatments. The digestive enzyme activity remained unaffected except amylase activity, which increased significantly in 50% SPLM replacement group (T2). Chymotrypsin decreased significantly (p